Decoding memory function through naturalistic gaze patterns - Jordana S. Wynn; Anisha Khosla; Arber Kacollja; Elaheh Shahmiri; Nicole D. Anderson; Kelly Shen; Jennifer D. Ryan (Proceedings of the National Academy of Sciences, 2025)
Eye movements are closely linked to encoding and retrieval processes, with changes in viewing behavior reflecting age- and pathology-related memory decline. In the current study, we leveraged this relationship to explore possible gaze-based indicators of memory function. Across two task-free viewing experiments, we investigated changes in naturalistic viewing behavior across five participant groups spanning a broad spectrum of memory function, from healthy young adults to amnesic cases. We show that memory decline is associated with an underlying reduction in explorative, adaptive, and differentiated visual sampling of the environment. Our results provide compelling evidence that naturalistic gaze patterns can serve as a sensitive marker of cognitive decline.